Konjunkturanalyse for Bornholm, 1987 til 1996 - lars Lund (Copenhagen Business School (CBS), Department of Economics, 2001)
– The paper gives an overview over four papers (chapters) dealing with the business cycle for the economy of Bornholm, 1987 to 1996. As a reference is used two regions in the capital area and the country as a whole. At the centre of interest is the labor market. The basic description is in chapter 1, and the model based treatment is in chapter 3. Prices and incomes are analysed with the purpose of finding regional prices and real incomes, chapter 2. These variables are used in the macroeconomic analysis in the following chapter. The employment on Bornholm is declining following a trend. Unemployment in the regions considered is increasing in relative terms. Nominal wages and incomes are influenced only to a small extent by the development of employment and the rate of unemployment. A special and short business cycle occurs for Bornholm during the years 1988-1990. Its origin seems to be a demand chock. The episode is treated in chapter
hdl:10398/7545
Keywords: R51; 330; Denmark; Business cycle; Bornholm